2008
DOI: 10.1158/1940-6207.capr-08-0055
|View full text |Cite
|
Sign up to set email alerts
|

NAD+-Dependent 15-Hydroxyprostaglandin Dehydrogenase Regulates Levels of Bioactive Lipids in Non–Small Cell Lung Cancer

Abstract: Elevated levels of procarcinogenic prostaglandins (PG) are found in a variety of human malignancies including non-small cell lung cancer (NSCLC). Overexpression of cyclooxygenase-2 and microsomal prostaglandin synthase 1 occurs in tumors and contributes to increased PG synthesis. NAD + -dependent 15-hydroxyprostaglandin dehydrogenase (15-PGDH), the key enzyme responsible for metabolic inactivation of PGs, is down-regulated in various malignancies. The main objective of this study was to elucidate the effect of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…We found that 100% of human lung tumor-tissue pairs showed a twofold decrease and that 61% showed a tenfold decrease in mRNA levels using quantitative reverse transcription polymerase chain reaction (RT-PCR) analysis [8]. Similar observation of the down-regulation of 15-PGDH in lung tumors was made in other laboratories [9,10]. Similarly, Yan et al [11] showed that median 15-PGDH expression of human colon cancer samples was at an undetectable level and was at least 17-fold below the median expression in normal colons using an assay on GeneChip expression microarrays.…”
Section: Is 15-pgdh Down-regulated In Tumors?supporting
confidence: 63%
“…We found that 100% of human lung tumor-tissue pairs showed a twofold decrease and that 61% showed a tenfold decrease in mRNA levels using quantitative reverse transcription polymerase chain reaction (RT-PCR) analysis [8]. Similar observation of the down-regulation of 15-PGDH in lung tumors was made in other laboratories [9,10]. Similarly, Yan et al [11] showed that median 15-PGDH expression of human colon cancer samples was at an undetectable level and was at least 17-fold below the median expression in normal colons using an assay on GeneChip expression microarrays.…”
Section: Is 15-pgdh Down-regulated In Tumors?supporting
confidence: 63%
“…In fact, previous work has suggested that the inhibition of tumor growth by PGDH expressing cells was due more to a regional effect of PGE2 reduction, such as reduced angiogenesis, and less on the direct effects on tumor cells. 11 Tumor PGDH expression clearly affects the tumor milieu, as shown by reduction of PGE2 levels in lung cancers 10 and alteration of antitumoral immune responses. 30 In our study, we show that PGDH knockdown in 9027 shRNA lentivirus-infected RT4 cells permitted PGE2 signaling as measured by cAMP generation, whereas signaling was suppressed in the PGDH-expressing parental lines ( Figure 3E).…”
Section: Discussionmentioning
confidence: 99%
“…9 PGDH expression has been shown to regulate PGE2 levels in lung cancer. 10 PGDH expression is reduced in colon, breast, gastric and lung cancers, and restoration can inhibit tumorigenesis in xenografts, thus PGDH is recognized as a tumor suppressor in those cancers. [11][12][13][14][15] Therefore, PGDH is important for regulating cancer development and progression.…”
mentioning
confidence: 99%
“…Collision-induced dissociation of the eicosanoids was performed using argon gas at a cell pressure of 1.6 × 10 Ϫ 3 Torr. Eicosanoids were detected and quantifi ed by multiple reaction mode monitoring of the transitions m/z 351 → 271 for AA-derived PGE 2 and m/z 353 → 317 for DGLA-derived PGE 1 ( 21 ).…”
Section: Fads1 Knockout Mouse Modelmentioning
confidence: 99%